Parapercis nigrodorsalis (Perciformes: Pinguipedidae), a new species of sandperch from northern New Zealand and the Norfolk Ridge, Tasman Sea and remarks on P. binivirgata (Waite, 1904) - Johnson, Jeffrey W.; Struthers, Carl D.; Wilmer, Jessica Worthington (Zootaxa, 2014)
A new species of pinguipedid fish, Parapercis nigrodorsalis, is described from 17 specimens collected off the North Island of New Zealand and Wanganella Bank, Norfolk Ridge, Tasman Sea, in depths of 56–280 m. The species has also been photographed underwater off the Poor Knights Islands Reserve and Burgess Island, Mokohinau Group, in New Zealand. It is most similar to Parapercis binivirgata (Waite, 1904) in morphology, coloration and meristic values, but is unique among the genus in having a combination of dorsal-fin rays V, 23, anal-fin rays I, 19, lateral-line scales 57–63, vomer with 1–2 irregular rows of robust conical teeth, palatines with 1–2 rows of small teeth, angle of subopercle smooth, 10 abdominal and 22 caudal vertebrae, and coloration, including seven broad reddish-brown bands on the upper body between the spinous dorsal-fin and the caudal peduncle, most bands bifurcated into close-set double bars with black smudge-like blotches below, and membrane of the spinous dorsal fin black. Comparison of the mitochondrial cytochrome c oxidase subunit 1 (CO 1) genetic marker utilised in DNA barcoding produced a genetic divergence of 5.38% and 7.63% between the new species and its two closest sampled congeners. The holotype of P. binivirgata is identified from two specimens previously regarded as syntypes, some revisions are made to meristic data in the original description of the latter, and a detailed description of the revised geographic range of P. binivirgata is provided.